Analysis of Relative Prosperity in Romania and Slovenia Using the Being-Loving-Having Model - Franci Cirkvenčič; Tine Bertoncel; Andrej Bertoncelj; Maja Meško (Amfiteatru Economic)
The study aimed to verify Allardt's prosperity model in the field of economic prosperity based on the notions of being, loving and having and to explore the existence of possible correlation among sets of all three variables. Canonical correlation analysis to predict relative prosperity was performed for selected 110 nations with the focus on Romania and Slovenia. The study results for Romania for 2011 indicate low approval of the government, low confidence in the judicial system as well as in financial institutions, in addition to concerns about health prospects and lack of confidence in the transparency of elections for the loving construct. In addition, the being construct is also negative in Romania suggesting overall dissatisfaction with the economic status and development, indicating strong dissatisfaction with governmental efforts to address poverty and efforts regarding sanitation, concerns about environment, existing standard of living and life expectancy, suggesting a weak health system. The study further suggests for Slovenia for 2011 negative expectations for the loving construct and below average expectations for the being construct. The approval of the government and confidence in the judicial system and financial institutions in Slovenia is also low, the only positive expectation is the confidence in electoral system, but Slovenians are also worried about their health prospects. In addition, the being construct for Slovenia is also slightly below average, indicating dissatisfaction with economic development and below average satisfaction with water quality and environment, and life expectancy suggesting health system inefficiency. The longitudinal study for the time period from 2011 till 2016 suggests moderate improvements for Romania in eight areas of relative prosperity, especially for the natural environment, governance and education, and for Slovenia practically unchanged situation. The study further suggests that both nations still face numerous challenges but due to implementation of certain structural reforms till 2016, albeit limited, some additional improvements regarding the economic prosperity of their citizens could be expected in the near future.